Functional Polymers for Controlled Drug Release - Spizzirri, Umile Gianfranco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue focuses on the synthesis and characterization of hydrogels specifically used as carriers of biological molecules for pharmaceutical and biomedical employments. Pharmaceutical applications of hydrophilic materials has emerged as one of the most significant trends in the area of nanotechnology. To propose some of the latest findings in this field, each contribution involves an in-depth analysis including different starting materials and their physico-chemical and biological properties with the aim of synthetizing high-performing devices for specific use. In this context, intelligent polymeric devices able to be morphologically modified in response to an internal or external stimulus, such as pH or temperature, have been actively pursued. In general, hydrophilic polymeric materials lead to high in vitro and/or in vivo therapeutic efficacy, with programmed site-specific feature showing remarkable potential for targeted therapy. This Special Issue serves to highlight and capture the contemporary progress in this field. Relevant resources and people to approach - American Association Pharmaceutical Scientists (AAPS): web: www.aaps.org; email: (marketing division): Marketing@aaps.org; (mmeting division): Meetings@aaps.org - International Association for Pharmaceutical Technology (APV): web: apv-mainz.de; email (managing director):